The level of environmental noise affects the physiological performance of Glycine max under water deficit - Bertolli, Suzana Chiari [UNESP]; Souza, Gustavo M. (Brazilian Soc Plant Physiology, 2013)
Plants in natural environments are subjected to a multitude of environmental cues. However, studies addressing physiological analyzes are usually focused on the isolation of a stress factor, making it difficult to understand plants behavior in their extremely complex natural environments. Herein, we analyzed how environmental variability (noise) may influence physiological processes of Glycine max under water deficit conditions. The plants were kept in a greenhouse (semi-controlled environment - E-SC) and in a growth chamber (controlled environment - E-C) under two water regime conditions (100 and 30% of replacement of the water lost by evapotranspiration) for 30 days. The environmental variability was daily monitored with automatic sensors to record temperature, humidity, and irradiance. The physiological responses were analyzed by leaf gas exchanges, chlorophyll fluorescence, biomembrane integrity, and growth parameters. The results showed that water deficiency caused significant reductions in the physiological parameters evaluated. However, the environment with high variability (E-SC) caused more extensive damages to biomembranes, regardless the water regime likely compromising physiological efficiency. The lower variability of E-C promoted higher efficiency of total biomass production in both water regimes compared to the E-SC. Therefore, our results support the hypothesis that more variable environmental conditions can limit the growth of Glycine max in response to the fluctuation of resources, therefore amplifying the effect of water deficit.
Keywords: controlled environment; environmental complexity; growth; photosynthesis; soybean